CULTURE AND CONNECTIONS PRELIMINARY RESEARCH AND PRESERVATIONRESTORATION INTERVENTIONS FOR WOOD ICONS - Pădurețu, Alexandrina; Gheorghiţă, Veronica (European Scientific Journal, ESJ, 2015)
The preservation-restoration intervention means making efficient again a product of human activity, the preservation consisting of multiple actions whose purpose is to treat and keep valuable cultural artifacts, both mobile and immobile. The restoration of works of art implies the establishment of a work methodology specific for each object, in compliance with general principles, the principle of minimum intervention being the basis of every methodological restoration proposals.The purpose of restoration is to restore the potential unity of the object. The restoration interventions must be recognizable without producing a historical or esthetic fake, reversible and performed with materials compatible with the original. For this reason, the first and most important action undertaken in order to treat a work of art is scientific documentation, consisting of analysis, tests, written, photographic and drawn documentation, all of these necessary in order to emphasize the technological aspects of the conservation status of the studied objects, as well as the proof of evolution of the performed interventions.The methodological preservation and restoration operations undertaken on the surface of the “Virgin Mary’s Entrance into the Church” icon from the Jitianu Monastery Collection (Craiova, Romania) have been done following a thorough scientific analysis and in accordance with the restoration principles. The purpose of the biological investigations has been to confirm the active attack of xylophagous insects, the recommendation being the treatment of the wood with a bioacid introduced in the flight orifices through injection and brushing. The physico-chemical investigations done through the FTIR (Fourier transform infrared spectroscopy) and XRF (X-ray fluorescence) techniques have shown degradations caused by the work technique, by identifying the type of primer and pigments used in the painting of the icon.The restoration interventions that have been undertaken have been thought and applied based on the types of degradation existing on the surface of the wooden structure and painting layer, following scientific research based on modern restoration principles, always and inalienably respecting the authenticity of the object. During the restoration process, the reversibility and compatibility with the original of the materials used, as well as the legibility of the interventions made.